To evaluate strength and motion range of internal and external rotational of the arm in even and ueven shoulder of volleyball players - Daneshjoo, Abdolrasoul; Mousavi Sadati , Seyed Kazem; Chamchamali , Salar (Journal of Clinical Physiotherapy Research, 2020)
Introduction: The shoulder joint is the most used joint in volleyball players. Performing repetitive movements and over-the-top attacks, the shoulder joint is under stress and leads to an asymmetrical shoulder and pain in the shoulder joint. The purpose of this study was to evaluate the strength and range of motion of internal and external rotating muscles in the asymmetric shoulder of the affected and non-volleyball players. Methods and Materials: This research is descriptive and causal-comparative. The statistical sample of this study was randomly assigned into two groups of affected and non-affected patients according to the research criteria. To measure the strength of the muscles of the rotator in two positions of zero and 45 degree shoulder from the dynamometer device (MMT), we used goniometer to measure the range of shoulder muscles and the scolymeter device was used as a symmetrical shoulder diagnostic tool. Results: There was a significant difference between the strength of internal (P=0/03) and external (P=0/02) rotating muscles in both non-diabetic and non-affected groups. Also, in this study, the internal (P=0/02) and external (P=0/03) spin amplitudes were significantly different in the two groups with and without asymmetric shoulder. Conclusion: The findings of this study showed that high muscle strength in asymmetric shoulder volleyball players is known as a risk factor in many studies. Limitations in the range of motion of the shoulder movements in the shoulder joint of asymmetric shoulder volleyball players require attention to preventive approaches by creating corrective strategies.